Antiosteoarthritis activities of 70% ethanol extract of Eleutherine bulbosa (mill.) urb. bulb on rats monosodium iodoacetate-induced osteoarthritis - Riza A. Sari; Fina Luthfiana; Irawati Sholihah; Katsuyoshi Matsunami; Sukardiman Sukardiman; Retno Widyowati (AOSIS, 2023)
Background: Osteoarthritis (OA) is a common degenerative joint situation that induces pain and disability in the elderly. Traditionally, Eleutherine bulbosa bulb from Pasuruan, East Java, is used to treat many diseases, also as an anti-inflammatory. Objective: In this research, we employed an in vivo model to examine the effects of 70% ethanol extracts of E. bulbosa (EBE) on the progression and development of OA. Methods: A singular intraarticular injection of Monosodium Iodoacetate (MIA) was used to create the OA model in rats. The progression of OA was observed for three weeks. Furthermore, treatment of EBE at a dose of 6, 12, and 24 mg/200g BW orally for four weeks was conducted to assess the effects on decreasing IL- 1ß level, joint swelling, and hyperalgesia. Results: Induction was successful, indicated by a significant difference (P0.05) in decreasing latency time, increasing joint swelling, and IL-1ß level. EBE 24 mg/200 g BW treatment has significantly (P0.05) reduced IL-1ß levels, joint swelling, and response to hyperalgesia. Conclusion: The 70% ethanol extract of E. bulbosa bulb has therapeutic effects on inflammation through reducing IL-1ß in experimental MIA-induced osteoarthritis in a rat model. According to this study, EBE may have an effective potential new agent for OA therapy.